Strategic Performance Evaluation Using Benchmarking Technique: Applied Research In The Sample Of Offices Of Inspectors General (Journal of Accounting and Financial Studies ( JAFS ), 2014)
In light of the rapid changes in the business environment and the entry of administrative leaders in the challenges of the atheist and twenty- increasing competition between sectors and the desire to acquire the skills, the traditional methods are no longer viable, which requires doing evaluates performance according to a more holistic, rather than limiting the performance evaluation on the financial hub that has not longer enough alone, as well as benchmarking method that has proven successful in developed countries as a way to develop and improve products and services.I've touched your search to the development of indicators evaluating the performance and preparation of a mechanism for making comparisons of reference between organizations contribute to achieving the desired objectives, this in his theory, but the practical side has touched search origination functions and duties of the offices of inspectors general , as well as an analytical study of the annual reports issued by the offices of inspectors general (sample), and application of indicators of performance evaluation on them, and then use those indicators as inputs to outputs forbenchmarking to identify the best partner, Google has come to a set of conclusions was the most important of the following :         helps integration and interdependence between the Vehicle Gauges strategic analysis of card balanced performance on the one hand and benchmarking on the other hand to strengthen the role of performance evaluation of strategic organizations by taking advantage of the advantages of Balanced Scorecard and method of benchmarking for the purpose of ruling on performance results in a more objective and clarity.In light of the foregoing, the search reached a set of recommendations was the most important are the following :        Create a section in the Office of Financial Supervision specialist to compare the reference shall be the process of evaluating the performance of offices of inspectors general and to begin identifying weaknesses first, and then diagnose and identify gaps, and conduct benchmarking with the offices of Arab and international view to proposing practices and new methods for the improvements , as well as providing technical assistance and advice and information necessary for offices for the purpose of applying benchmarking method successfully.